Produtividade do tomateiro cultivado em ambiente protegido irrigado com água enriquecida com CO2 - Grabowski, Marta Marivania Soranço (2010)
The experiment was conducted at Unioeste Campus Rondon-PR, at the Experimental Station of Horticulture and Biological Control, Professor Mario Cesar Lopez. This study aimed to evaluate the characteristics of tomato production in greenhouse under four doses of carbon dioxide applied by irrigation, drip. Two experiments were conducted, the first experiment was conducted in spring / summer 2008/2009 and the second winter / spring 2009. We used a randomized design in factorial four x four, with three replications. We used four levels of CO2 (0, 4, 7 and 10 L min-1) and four hybrids of tomato (Alhambra, Jennifer, Sheila and Lumi). CO2 was applied daily through irrigation water for 15 days after transplantation until the end of the cycle. The irrigation were executed daily at 10 o clock during 15 minutes and 15 o clock during 15 minutes, 15 days after the plants transplantation. We selected six plants per plot for conducting evaluations in the first experiment and three in the second. The fruits were collected, and evaluated the transverse and longitudinal diameter of fruit, commercial production of fruits, commercial fruits yield, commercial no production of fruits and commercial no fruit yield. Commercial productivity of fruit production and total yield, fruit number of commercial fruits, number of unmarketable fruits, number of fruit total number of fruits with blossom-end rot, acidity, soluble solids and pH. In the first experiment, the application of carbon dioxide through irrigation water, reduced yield and marketable yield and total for hybrids Alhambra and Jennifer; increased the soluble solids and acidity for hybrids and Sheila Lumi. The hybrid Alambra outranked the other hybrids showed the highest production of marketable fruit and the hybrid-emphasized Jennifer showed the highest diameter of fruit and average fruit trade. In the second experiment, the application of carbon dioxide through irrigation water reduced the production and marketable yield and total fruit, fruit number and total trade, average fruit commercial fruit and transverse diameter of the fruits of all hybrids. The use of CO2 through water irrigation increased acidity of fruits. There was no difference of hybrids for commercial production and productivity and total between hybrids. However, the hybrid Jennifer got greater and greater fruit weight diameter of fruit, so you can get better ratings